Origen in the Likeness of Philo: Eusebius of Caesarea’s Portrait of the Model Scholar - Rogers, Justin M. (Studies in Christian-Jewish Relations, 2017)
This article discusses the similarities between the biographical presentations of Philo and Origen in Eusebius' Ecclesiastical History. The tension Eusebius feels between Philo Christianus and Philo Judaeus is certainly detectible in his presentation of the Therapeutae, a group about whom Philo reports and whom Eusebius considers the first Egyptian Christians. Eusebius recognizes that Philo is exegetically closer to Christianity, and religiously closer to Judaism. This realization creates an ambiguity in the Ecclesiastical History in which Philo is presented explicitly neither as Jew nor Christian, but can be identified as either.